Optimizing the Principal's Role as Learning Supervisor to Enhance Teacher Performance in Elementary Schools - Tismegadewi, Tismegadewi; Hendrizal, Hendrizal; Aisyah, Siti; Kurniawan, Romi (Universitas Negeri Makassar, 2026)
This study examines the optimization of elementary school principals’ roles as learning supervisors to enhance teacher performance in Siulak Mukai District. Using a qualitative descriptive approach, data were collected through non-participatory observation, semi-structured interviews, and document analysis involving seven principals and seven teachers across seven schools. Results indicate that principals implement structured, participatory supervision utilizing classroom visits, individual coaching, and peer observation. Reflective feedback is consistently provided within one day post-observation. Teacher performance shows marked improvement across quality, quantity, timeliness, resource efficiency, autonomy, and collaborative engagement. Key optimization strategies include needs-based professional development, non-material recognition, flexible scheduling, and contextual adaptation to infrastructural constraints. The study concludes that reframing academic supervision from administrative inspection to continuous professional mentoring significantly elevates teacher performance and cultivates a collaborative school culture. Sustainable supervision in resource-limited settings requires adaptive leadership, systematic follow-up, and contextual flexibility. These findings highlight the critical role of instructional coaching in fostering teacher professionalism and improving educational outcomes.